Studi Literatur Implementasi Experiental Learning untuk Meningkatkan Kemandirian Siswa - Nurfadhilah, Alifah Aulia; Evi Setia Ningsih; Niken Nurrohmawati; Vindika Rahayu Wilujeng; Aftin Nazakia; Taufik Muhtarom (Indo-MathEdu Intellectuals Journal, 2025)
Student independence is one of the important indicators in character development and learning ability. However, many students still rely on conventional teaching and are less able to manage the learning process independently. The main problem that needs to be studied is how the application of experiential learning principles can help students develop an independent attitude in learning. This study aims to examine the implementation of experimental learning in improving student independence. This study uses a descriptive qualitative method with a literature study to analyze the concept of experiential learning and student independence based on previous research findings in the context of education. The results of the study show that this approach encourages students to develop problem-solving skills, creativity, and the ability to make decisions independently. In addition, experimental learning also plays a role in increasing students' self-confidence and responsibility for their learning process. It is hoped that the results of this study can be a reference for educators in designing more effective learning to improve student independence.